The Relationship between Internet Addiction and Academic Success of Secondary School Students - Turel, Yalin Kilic; Toraman, Muhammet (Kamla-Raj Enterprises, 2015)
This study aims to determine the relationship between the Internet addiction level of secondary school students and their academic performance. A qualitative and correlational research model was used to analyze the data. Participants in the study were 10(th), 11(th) and 12(th) graders from nine secondary schools in Istanbul, Turkey, totaling 1,302 students. A personal information form and an Internet Addiction Scale were used as data collection tools. In addition, students' academic grades were provided by school managements and added to the personal information forms. Based on the results, it was found that Internet addiction had an effect on the academic achievements of students. It was found that as the academic success of the students deemed academically successful (45 and up in terms of grades) increases, their Internet addiction averages decreases. In addition, the average Internet addiction levels of male students, vocational school students and verbal field students were determined to be higher than more academically successful students.
Keywords: Internet Use; Academic Achievement; Secondary Schools; Addiction; Measures